Iraqi Press Framing of political discourse in the aftermath of declaration of victory over ISIS: An analytical study of Assabah, Azzaman, and Tareek alshaab newspapers - Qasim Thamer, Alyaa; Sabeeh Ghintab, Azhar (Al-Adab Journal, 2020)
The research sought to achieve several goals from which are: identifying the quantity of news that dealt with the political discourse of Iraqi PM in the Iraqi newspapers (Assabah, Azzaman, and Tareek alshaab). Identifying issues of political discourse, uncovering the news frames employed by the newspapers while giving salience to issues of political discourse that received most of their attention, in addition to testing validity of the research hypotheses that were that assumed existence of statistically significant differences between the newspapers in employing the news sources and salience elements in framing political discourse. The research is descriptive and it adopted the survey method to describe and analyze a comprehensive sample of (657) issues from the three newspapers from 12/10/2017 to 10/25/2018, and it used coding scheme as a tool. The research has reached several conclusions: the newspapers showed great variance in the interest with the political discourse of the Iraqi PM with the semi-official press have showed the greatest, followed by the partisan press, and the private press recorded the least. The newspapers have varied in their interest with the political issues, with Assabah showed most interest with construction issue, Azzaman with corruption, and Tareek alshaab with elections, taking into account the variation in their priorities, as responsibility and economic consequences frames were adopted in presenting reconstruction issues, and responsibility and conflict frames in election and corruption issues. Also, there were statistically significant differences among the newspapers in employing the news sources and salience elements {partially} that framed the political discourse of the PM.